Penggunaan Media Video dan Power Point dalam Penyuluhan Daring tentang Karies Gigi - Yovita Kurnia Dewi; Isnanto Isnanto; Endang Purwaningsih; Imam Sarwo Edi; Silvia Prasetyowati (FORIKES, 2022)
Dental caries is a dental health problem that often occurs in elementary school students. During the pandemic, the face-to-face learning system became online learning, so that efforts to increase knowledge about dental and oral health can be carried out using video media and power points. This study aims to determine differences in the effectiveness of using video media and power point in online counseling to increase knowledge about dental caries in fifth grade students at SDN Wage 1 Sidoarjo during the Covid-19 pandemic. The research design was pretest-posttest with control group, which involved 70 students. The data collection instrument was a questionnaire. Data were analyzed using independent sample t test. The results of the study show that power point is more effective as an online extension medium.Keywords: dental health; knowledge; online counseling; videos; power point ABSTRAK Karies gigi merupakan masalah kesehatan gigi yang banyak terjadi pada siswa sekolah dasar. Dalam masa pandemi, sistem pembelajaran tatap muka menjadi pembelajaran online, sehingga upaya peningkatan pengetahuan tentang kesehatan gigi dan mulut dapat dilaksanakan dengan menggunakan media video dan power point. Penelitian ini bertujuan untuk mengetahui perbedaan efektifitas penggunaan media video dan power point dalam penyuluhan online untuk meningkatkan pengetahuan tentang karies gigi pada siswa kelas V SDN Wage 1 Sidoarjo pada masa pandemi Covid-19. Rancangan penelitian ini adalah pretest-posttest with control group, yang melibatkan 70 siswa. Instrumen pengumpulan data adalah kuesioner. Data dianalisis menggunakan independent sample t test. Hasil penelitian menunjukkan bahwa power point lebih efektif sebagai media penyuluhan online.Kata kunci: kesehatan gigi; pengetahuan; penyuluhan online; video; power point